Effect of nordihydroguaiaretic acid on cell viability and glucose transport in human leukemic cell lines. Issue 10 (23rd August 2016) - Leon, David; Parada, Daniela; Vargas‐Uribe, Mauricio; Perez, Alejandra A.; Ojeda, Lorena; Zambrano, Angara; Reyes, Alejandro M.; Salas, Mónica
Abstract : The polyphenol nordihydroguaiaretic acid (NDGA) has antineoplastic properties, hence it is critical to understand its action at the molecular level. Here, we establish that NDGA inhibits glucose uptake and cell viability in leukemic HL‐60 and U‐937 cell lines. We monitored hexose uptake using radio‐labeled 2‐deoxyglucose (2DG) and found that the inhibition by NDGA followed a noncompetitive mechanism. In addition, NDGA blocked hexose transport in human red blood cells and displaced prebound cytochalasin B from erythrocyte ghosts, suggesting a direct interaction with the glucose transporter GLUT1. We propose a model for the mechanism of action of NDGA on glucose uptake. Our study shows for the first time that NDGA can act as inhibitor of the glucose transporter GLUT1. Abstract : The natural polyphenol nordihydroguaiaretic acid (NDGA) exhibits antineoplastic properties but the molecular mechanism is not well understood. Here, we demonstrate that NDGA blocks glucose uptake by direct interaction with the hexose transporter GLUT1. NDGA follows a noncompetitive mechanism of inhibition and decreases viability of leukemic cell lines.